Linking Empowering Leadership, Psychological Empowerment, Self-Leadership, Creative Involvement and Creativity: A Sequential Mediation Model - Ishfaq Ahmed; Muhammad Khalid Khan; Ghulam Ali Bhatti (The Lahore Journal of Business)
This study examines the relationship between empowering leadership and employee creativity through the serial mediating role of psychological empowerment and self-leadership with creative work involvement. Applying a chain mediation approach to a sample of 314 respondents, we find that empowering leadership has a significant effect on the selected mediators (self-leadership, psychological empowerment and creative work involvement), which in turn transfer this effect to employee creativity.